Impact of pneumonitis from radiotherapy combined with immune checkpoint inhibitors therapy on tumor progression and survival in patients with non-small cell lung cancer - Wang, Ziwei; Xu, Kunpeng; Sun, Han; Liang, Jun; Jiang, Wei; Wang, Luhua (Frontiers in Immunology, 2025)
PurposeThis study evaluates the impact of thoracic radiotherapy (TRT) combined with immune checkpoint inhibitors (ICIs) treatment-related pneumonitis on tumor progression and prognosis in patients with non-small cell lung cancer (NSCLC).MethodsData were collected retrospectively from NSCLC patients treated with TRT and ICIs between January 2019 and August 2023. Treatment-related pneumonitis (TRP) was assessed and graded using the Common Terminology Criteria for Adverse Events (CTCAE) and the Chinese Society of Clinical Oncology Guidelines for Managing Immunotherapy-Related Toxicities. Kaplan-Meier curves and log-rank tests examined associations between pneumonitis with local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), progression-free survival (PFS), and overall survival (OS). COX regression identified prognostic factors in the pneumonitis group.ResultsAmong 86 patients, 58 (67.4%) developed TRP, including 37.2% with grade 2 pneumonitis, and no grade ≥3 cases. 12 patients (14.0%) developed mixed radiation and ICIs pneumonitis. The pneumonitis group had significantly shorter DMFS (12.07 vs not reached, p = 0.028) and PFS (9.53 vs 14.27 months, p = 0.040), shorter LRFS compared to the non-pneumonitis group, but similar OS. High-grade pneumonitis correlated with worse outcomes, especially DMFS (p = 0.031), basically no differences among pneumonitis types. Multivariate COX analysis identified solitary pulmonary nodules or masses as independent negative prognostic factors for PFS, while higher MLD (mean lung dose) independently predicted reduced OS.ConclusionPneumonitis resulting from TRT combined with ICIs was associated with shorter PFS but did not affect OS in NSCLC patients. Mixed pneumonitis did not worsen outcomes. Larger prospective studies are needed to validate these findings.